Estresse e zumbido: o relaxamento como uma possibilidade de intervenção - Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Viana, Nathalia Perfumo Munhoz [UNESP]; Palamin, Maria Estela Guadagnucci [UNESP]; Calais, Sandra Leal [UNESP] (GN1 Sistemas e Publicacoes, 2014)
The aim of this study was verify the stress on people with tinnitus and the effect of progressive relaxation to modify the perception of tinnitus and reduce the stress. The stress was tested in 50 patients and the intervention was done with 12 people in the sample. In this interview was used the history, symptom inventory stress and progressive relaxation. The results demonstrate that the tinnitus affects the patient’s life in physical and emotional aspects. The intervention with the progressive relaxation showed satisfactory answers such as modification in the perception of tinnitus and stress symptoms. The psychological intervention contributed with how the patients will deal with tinnitus, leading them to learning strategies and coping with the stress and the symptoms.

El objetivo de esta investigación fue verificar la presencia de estrés de personas con queja de zumbido y el efecto del relajamiento progresivo con su reducción. El estrés fue evaluado en 50 pacientes y la intervención se llevó a cabo con 12 participantes en la muestra. Se utilizó la entrevista de anamnesis, el inventario de síntomas de estrés y el relajamiento progresivo. Los resultados mostraron que el zumbido afecta a las vidas de los pacientes en aspectos físicos y emocionales. La intervención con el relajamiento progresivo reveló respuestas satisfactorias como cambios en la percepción del zumbido y en los síntomas de estrés. La intervención psicológica contribuyó en el control de los pacientes en comparación con la convivencia con el zumbido, lo que lleva al aprendizaje de estrategias de enfrentamiento del síntoma y del estrés.

O objetivo desta pesquisa foi verificar a presença de estresse em pessoas com queixa de zumbido e o efeito do relaxamento progressivo na percepção do zumbido e no estresse. O estresse foi avaliado em 50 pacientes, e a intervenção ocorreu com 12 participantes da amostra. Utilizaram-se a entrevista de anamnese, o inventário de sintomas de stress e o relaxamento progressivo. Os resultados demonstraram que o zumbido influencia a vida dos pacientes em aspectos físicos e emocionais. A interven- ção com o relaxamento progressivo revelou respostas satisfatórias como alterações na percepção do zumbido e nos sintomas de estresse. A intervenção psicológica contribuiu para o controle dos pacientes em relação ao convívio com o zumbido, conduzindo-os ao aprendizado de estratégias de enfrentamento ao sintoma e ao estresse.
Stress and tinnitus: relaxation as a possibility of intervention
El estrés y el zumbido: el relajamiento como una posible intervención
Keywords: Stress; Tinnitus; Progressive relaxation; Group intervention; Clinical intervention; Estrés; Zumbido; Relajamiento progresivo; Intervención en grupo; Intervención clínica; Estresse; Zumbido; Relaxamento progressivo; Intervenção em grupo; Intervenção psicológica